2008
DOI: 10.1016/j.orggeochem.2007.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for substantial intramolecular heterogeneity in the stable carbon isotopic composition of phytol in photoautotrophic organisms

Abstract: The ubiquitous isoprenoid phytol was isolated from a range of algae, terrestrial plants and a bacterium and its two terminal carbon atoms were quantitatively removed by chemical oxidation. The product, 6,10,14-trimethylpentadecan-2-one, was depleted in 13 C by 1-4‰ relative to the parent phytol. This difference is significant, and indicates that the pathway for biosynthesis of phytol induces substantial intramolecular stable carbon isotopic fractionations. The nature and magnitude of the fractionations suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…5‰ depleted in 13 C relative to FA in the photoheterotrophic culture (Table , Figure ). The 2‰ enrichment relative to n ‐alkyl lipids in the photoautotrophic culture is consistent with other reports of CO 2 ‐fixing organisms (Hayes, ; Sakata et al., ; Schouten et al., , ). The only report of which we are aware that compares phytol 13 C patterns for photoheterotrophy versus photoautotrophy is for the related taxon, Chromatium tepidum (Madigan, Takigiku, Lee, Gest, & Hayes, ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…5‰ depleted in 13 C relative to FA in the photoheterotrophic culture (Table , Figure ). The 2‰ enrichment relative to n ‐alkyl lipids in the photoautotrophic culture is consistent with other reports of CO 2 ‐fixing organisms (Hayes, ; Sakata et al., ; Schouten et al., , ). The only report of which we are aware that compares phytol 13 C patterns for photoheterotrophy versus photoautotrophy is for the related taxon, Chromatium tepidum (Madigan, Takigiku, Lee, Gest, & Hayes, ).…”
Section: Resultssupporting
confidence: 91%
“…Other discussions of the relative 13 C patterns between isoprenoids and biomass have focused largely on eukaryotic algae (e.g., Schouten et al., , ). Although more complicated to interpret than bacteria, some of the same principles may apply.…”
Section: Resultsmentioning
confidence: 99%
“…5 and Table 1), which might occur naturally due to the intramolecular isotopic heterogeneity of the parent compound, phytol, during loss of a C atom (cf. Schouten et al, 2008); an analogous effect has been observed for 6,10,14-trimethylpentadecan-2-one, which was depleted in 13 C relative to its parent compound, phytol, by 1-4‰ (cf. Schouten et al, 2008).…”
Section: Source Of Isoprenoid Hydrocarbons In Sediments Above and Belmentioning
confidence: 53%
“…Schouten et al, 2008); an analogous effect has been observed for 6,10,14-trimethylpentadecan-2-one, which was depleted in 13 C relative to its parent compound, phytol, by 1-4‰ (cf. Schouten et al, 2008). Plausible source organisms for the C 21-25 head-to-tail linked isoprenoid hydrocarbons are halophilic archaea (e.g.…”
Section: Source Of Isoprenoid Hydrocarbons In Sediments Above and Belmentioning
confidence: 53%
“…PYT moieties are formed both through MVA (mevalonic acid) [32e34] and MEP (2-C-methylerythritol-4-phosphate) pathways [29,35] (Fig. 4).…”
Section: Biosynthesis and Metabolismmentioning
confidence: 99%